PENGKAJIAN KINERJA HIDRAULIK BANGUNAN PELIMPAH BENDUNGAN SANTAN DI KALIMANTAN TIMUR - Kumala, Yiniarti Eka (Jurnal Teknik Sipil ITENAS, 2007)
Santan dam is designed to be built in Santan river for supply water of Bontang city in East Kalimantan Province. The contruction of Santan dam is intended to anticipate the development of Bontang city in the next twenty years to be an industrial and mining city. The spillway of the dam is designed using side channel spillway provided by straight chute cannel and USBR II Stilling basin. The objectives of the hydraulic design study for the spillway are to evaluate and to achieve the perfect, safe and optimum hydraulic design of the spillway. The study method is conducted by physical hydraulic model investigation in the laboratory. The model is an undistorted model with geometric same both in horizontal and vertical direction, to be selected as 1 to 40. Based on the study results, it is concluded that the hydraulic performance of the original design in less, because there are some eddies unsptream of the crest, some cross waves in the chute channel and the stilling basin doesnot effectively dissipate the energy. In order to perfect the hydraulic design, it is recommended to modify the upstream guide walls, side channel spillway, chute channel and the stilling basin.